The effect of melanocortin 4 receptor agonist RM-493 on cognitive functions in rats fed with western diet - (:unkn) unknown (My University, 2023)
Background: The central melanocortin system is among those that plays a key role in the homeostatic regulation of energy balance and eating disorders. This study investigated the effect of melanocortin 4 receptor (MC4R) agonist setmelanotide (RM-493) on changes in metabolic and cognitive functions. Methods: Thirty two male Sprague-Dawley rats were divided into 4 groups including those fed with standard laboratory food and given phosphate buffered saline (PBS, ND group); fed with western-type diet and given PBS (WD group); fed with standard laboratory food and given RM-493 (RM-493 group); and fed with western-type diet and RM-493 (WD+RM-493 group). After injection with PBS and RM-493 injections for 5 days, they were followed by elevated plus maze test and a novel object recognition test. Results: Nutrition with western-type diet resulted in an increase in serum cholesterol, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) levels, respectively, and RM-493 treatment decreased these values. Proopiomelanocortin (POMC), MC4R and brain-derived neurotrophic factor (BDNF) expressions increased in groups fed with western-type diet and RM-493. Treatment with RM-493 in ND group increased the residence time in the open arm. In WD group, CA3 region of the hippocampus revealed edema in stratum lucidum layer and degeneration in the pyramidal neurons unlike the WD+RM-493 group. Conclusion: POMC-mediated pathway was activated as a result of an increase in body fat caused by a western-type diet. RM-493 had alleviating effects on brain damages caused by a western-type diet and could improve cognitive functions.
Keywords: Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Sağlık Bilimleri; Mühendislik ve Teknoloji; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Food Engineering; Health Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Tarım Bilimleri; BESLENME VE DİYETETİK; GIDA BİLİMİ VE TEKNOLOJİSİ; Agriculture & Environment Sciences (AGE); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; FOOD SCIENCE & TECHNOLOGY; Yemek bilimi; Yaşam Bilimleri; Beslenme ve Diyetetik; Food Science; Life Sciences; Brain; Cognitive functions; MC4R; RM-493; Western diet